Multilevel control of run orientation in Drosophila larval chemotaxis - Gomez-Marin, Alex; Louis, Matthieu (Frontiers in Behavioral Neuroscience, 2014)
Chemotaxis is a powerful paradigm to study how orientation behavior is driven by sensory stimulation. Drosophila larvae navigate odor gradients by controlling the duration of their runs and the direction of their turns. Straight runs and wide-amplitude turns represent two extremes of a behavioral continuum. Here we establish that, on average, runs curl toward the direction of higher odor concentrations. We find that the orientation and strength of the local odor gradient perpendicular to the direction of motion modulates the orientation of individual runs in a gradual manner. We discuss how this error-correction mechanism, called weathervaning, contributes to larval chemotaxis. We use larvae with genetically modified olfactory systems to demonstrate that unilateral function restricted to a single olfactory sensory neuron is sufficient to direct weathervaning. Our finding that bilateral sensing is not necessary to control weathervaning highlights the role of temporal sampling. A correlative analysis between sensory inputs and behavioral outputs suggest that weathervaning results from low-amplitude head casts implemented without interruption of the run. In addition, we report the involvement of a sensorimotor memory arising from previous reorientation events. Together, our results indicate that larval chemotaxis combines concurrent orientation strategies that involve complex computations on different timescales.